Everolimus-Induced Antineutrophil Cytoplasmic Antibody Associated Vasculitis in Metastatic Renal Cell Carcinoma: A Case Report - Hanadi M. Alhozali, (Journal of King Abdulaziz University: Medical Sciences, 2023)
This is a case report of a 67-years-old male with metastatic renal cell carcinoma presented with pancytopenia, pneumonitis, and an acute on chronic renal failure. He was initiated on Everolimus four weeks earlier. Further work-up did not reveal pre renal or post renal components which accounted for his renal failure. Serological studies showed positive antineutrophil cytoplasmic antibody; directed against proteinase 3-antineutrophil cytoplasmic antibodyand myeloperoxidase. Interestingly, the renal function did not improve after discontinuation of Everolimus and the patient was initiated on hemodialysis. Immunosuppressive therapy consisting of steroid and Cyclophosphamide was started based on clinical features and laboratory data. Unfortunately, diagnostic kidney biopsy was contraindicated, given that he had only a single kidney from previous nephrectomy for renal cell carcinoma. Ultimately, renal function and urine output recovery occurred after two doses of IV cyclophosphamide. In conclusion, this case represents Everolimus-induced antineutrophil cytoplasmic antibody associated vasculitis with severe renal involvement; features that were not previously described in the literature regarding this drug. Thus, the possibility of Everolimus-induced antineutrophil cytoplasmic antibody vasculitis should be considered when patients treated with Everolimus develop severe renal insufficiency that cannot be explained by other etiologies.